Positive Affirmations to Reduce Anxiety Levels in Primigravida Pregnant Women in the Sukaraya Community Health Center Work Area - Setyoputri, Zahrotun Nisa’ (Papua Medicine and Health Science, 2025)
Primigravida pregnant women, namely those experiencing pregnancy for the first time, generally undergo physical and psychological changes that may trigger worry and anxiety, as pregnancy is a new experience. Such conditions can have adverse impacts, including stimulating uterine contractions, increasing the risk of complications, and impairing maternal well-being. One non-pharmacological approach to reduce anxiety is the application of positive affirmations. This study aimed to describe the implementation of positive affirmations in reducing anxiety levels among primigravida pregnant women at the Sukaraya Community Health Center. A descriptive case study design was employed, involving two primigravida pregnant women from April 20–24, 2025. Research instruments included the Perinatal Anxiety Screening Scale (PASS) questionnaire and observation sheets. The findings revealed that prior to the intervention, both subjects experienced severe anxiety; however, after five consecutive days of positive affirmation intervention, their anxiety levels decreased significantly. These findings suggest that positive affirmations can serve as a simple intervention applicable in healthcare services to help reduce anxiety levels in pregnant women, particularly those who are primigravida.